2020
DOI: 10.1002/er.5447
|View full text |Cite
|
Sign up to set email alerts
|

Layered molybdenum disulfide coated carbon hollow spheres synthesized through supramolecular self‐assembly applied to supercapacitors

Abstract: Summary Through supramolecular assembly method, molybdenum disulfide (MoS2) is uniformly anchored on the mesoporous hollow carbon spheres (HCS), which are obtained by hard template method. The introduction of HCS can prevent the agglomeration of MoS2 and decrease the electric resistance of the compound material MoS2@HCS. The composite of MoS2@HCS‐17 also owns a specific surface area of 119.0 m2 g−1. For MoS2@HCS‐17, SEM and TEM results exhibit that flaky MoS2 is uniformly covered on hollow carbon spheres and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The highest power density obtained for the same was 5556.2 W kg −1 . [145] The corresponding specific surface areas of all the electrode materials presented in Table 1 have been plotted in Figure 5a. Similarly, Figure 5b-e draws a comparison among the unconventional and conventional electrode systems based on the specific capacitances and average pore sizes of the electrodes, as well as the maximum energy densities, and maximum power densities (also presented in Table 1) of the as-designed supercapacitor devices, respectively.…”
Section: Comparison With Conventional Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest power density obtained for the same was 5556.2 W kg −1 . [145] The corresponding specific surface areas of all the electrode materials presented in Table 1 have been plotted in Figure 5a. Similarly, Figure 5b-e draws a comparison among the unconventional and conventional electrode systems based on the specific capacitances and average pore sizes of the electrodes, as well as the maximum energy densities, and maximum power densities (also presented in Table 1) of the as-designed supercapacitor devices, respectively.…”
Section: Comparison With Conventional Electrodesmentioning
confidence: 99%
“…[ 131–136 ] Predominantly, these materials include carbon nanotubes (CNTs), graphene, carbon spheres, hollow carbon spheres, carbon nanoparticles (CNPs), etc. [ 62,137–145 ] Nevertheless, they fail to demonstrate the desirable performance in practical applications after a certain threshold owing to their short durability and low energy density. Although, metal‐organic frameworks (MOFs) have proven to be better electrode candidates in certain aspects, [ 142,143,146–148 ] however, these materials incur high cost, low yield of porous carbon, high consumption of metallic nitrate, [ 62 ] and hence higher waste generation.…”
Section: Solid Waste Materials In Supercapacitor Fabricationmentioning
confidence: 99%
“…Much work has been done to overcome this problem, like the combination of MoS 2 with carbonaceous materials and CPs. [30][31][32] Recent studies have shown that MoS 2 /PEDOT:PSS electrode composites are particularly interesting because they can lead to high capacitances due to the pseudocapacitive effect of both materials. Ge et al 33 reported a supercapacitor electrode based on MoS 2 / PEDOT:PSS composite films produced by filtration with a great volumetric capacitance of 141.4 F cm −3 and remarkably long-term cyclability (98.6%).…”
Section: Introductionmentioning
confidence: 99%
“…One of the many drawbacks of using MoS 2 as supercapacitors electrodes is its low conductivity. Much work has been done to overcome this problem, like the combination of MoS 2 with carbonaceous materials and CPs 30‐32 …”
Section: Introductionmentioning
confidence: 99%
“…which are advantageous for improving the contact of the electrode with electrolyte and providing much shorter transport pathways for electrolyte ions and electrons. 13,14 These advantages endow porous and hollow carbon materials with excellent rate performances and long cycling stability. Generally, the used electrode materials are nonrenewable and/or involve complicated preparation processes and high costs.…”
mentioning
confidence: 99%